Is Violence, Violence no Matter Where it Strikes? Adjudicated Boys, Thwarted Belongingness, Perceived Burdensomeness, and Acquired Capability for Suicide - Van Wyk, Judy A. (Journal of interpersonal violence, 2022)
This study explores treating violence against others as a precursor to self-directed violence. It tests the utility of including violence against others in the measure of acquired capability to test assumptions from the interpersonal theory of violence. Four theoretical hypotheses are assessed that are consistent with the theory: (1) thwarted belongingness (parental abandonment and rejection) and perceived burdensomeness (exposure to parental interpersonal violence and child abuse) independently increase the likelihood of suicidal ideation; (2) the interaction of thwarted belongingness and perceived burdensomeness increases the likelihood of suicidal ideation controlling for other pertinent variables; (3) the three-way interaction of thwarted belongingness, perceived burdensomeness, and acquired capability (violence against others and prior suicidal attempts) increases the likelihood of suicidal attempts controlling for other pertinent variables; and (4) self-harm responds to the theoretical variables and similarly, to attempts. Subjects are court-adjudicated males (ages 13?18) who were residents for up to 1 year at the Ocean Tides School and rehabilitation center from 1975?2019. The data span 44 years and include 2195 youth. Depression, drug/alcohol use, race, ethnicity, socioeconomic status, and interaction terms between SES and race and SES and ethnicity are also examined. Backward conditional logistic regression analyses find mixed support for the hypotheses, but strong support for including violence against others in the concept of acquired capability. Support is also found for conceptualizing child abuse and exposure to parental interpersonal violence as perceived burdensomeness in tests of this theory as well as measures of depression. Major implications for programming in the treatment and rehabilitation of delinquent boys include conceptualizing and approaching violence against others as a precursor to suicidal attempts and other self-directed harm.